Effect of Leaf Cuttings and Nutrient Levels on Growth, Yield and Quality of Seed in Palak (Beta vulgaris var. bengalensis) - SHUBHAM MALVIYA; SS KUSHWAH; RK SHARMA; BK KACHOULI (Seed Research, 2026)
A field investigation was conducted at Bahadari Farm, College of Horticulture, Mandsaur (MP) during the Rabi, 2021-22. Twelve treatment combinations comprising of three leaf cutting levels viz., C1 (No cutting), C2 (One cutting) and C3 (two cuttings) and four nutrient levels viz., F1 (No Fertilizer), F2 (50 kg N+40 kg P2O5+ 30 kg K2O), F3 (75 kg N+60 kgP2O5+45kgK2O) and F4 (100 kg N+80 kg P2O5+60 kg K2O) were tested in factorial randomized block design with three replications. Observations were recorded on plant height, number of leaves, leaf area per plant, fresh and dry weight of shoot per plant, number of spikes per plant, length of spike, number of seed per spike, leaf yield, seed yield, germination, test weight, seedling vigour index-I and seedling vigour index-II. Economics of different treatments was calculated in terms of gross and net return as well as benefit: cost ratio. The findings of the experiment revealed that number of leaf cuttings, nutrient levels as well as their combined effect had significant effect on all the growth, yield and seed quality parameters but no effect on plant height, number of leaves, length of spike and seedling vigour index-I which indicated non significant influence of combined effect of leaf cuttings and nutrient levels. Highest leaf yield (136.11/ha) was noted with C3F4 which was at par with the C3F3 (117.77q/ha). Rest of the treatments had significantly lower leaf yield as compared to C3F4. Application of C2F3 had recorded highest seed yield (25.23q/ha) which was at par with C2F4 (24.87q/ha). Rest of the treatments had significantly lower seed yield as compared to C2F3. Highest gross return (Rs. 691300), net return (Rs.647155) as well as B:C ratio(14.66) were realized with C2F3.